(untitled) (Mongolian Journal of Agricultural Sciences, 2022)
Seed size is an important parameter that can influence the germination, growth, and biomass of nursery seedlings and future crops. In this study, the effect of seed size on germination and grain yield was analyzed in six different wheat varieties (early maturity Darkhan-131, Darkhan-160, mid-early maturity Darkhan-34, Darkhan-193, mid-late maturity Darkhan-144, Darkhan-181). Based on diameter, the seeds were categorized into five size classes (>2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm, <3.0 mm) by an analytical sieve machine HAVER EML 200 and planted in a 1m2 plot. The study had three replications. Results of this study showed that the germination rate of medium and larger-sized seeds (<2.2 mm) increased by 7.3-15.0%, but decreased by 14.4-27.3% for smaller-sized seeds (>2.2 mm). The enlarged seed size classes from 2.0 mm to 2.8 mm had an increase in crop yield by 0.49 t/ha. We also found that seed size significantly affected the germination rate and grain yield (F=2.374, P≤0.00). Regression analysis showed that enlarging seed sizes by 0.1 mm increased grain yield by 2.12%. Among all the varieties, the enlarged seed sizes (greater than 2.2 mm) influenced the emergence and yield more so than the smaller seed sizes (less than 2.2 mm), especially in mid-early and mid-late maturity varieties. Results demonstrate that larger seed sizes (>2.2 mm) can be more useful for early-maturity varieties, and smaller seed sizes (>2.5 mm) are more relevant for mid-early and mid-late maturity varieties. Буудайн тарих үрийн тохиромжтой фракцыг тогтоох Хураангуй Үрийн фракц нь хээрийн цухуйц, биомасс, ургацад нөлөөлдөг тарих үрийн чанарын чухал үзүүлэлт болно. Эндоспермдээ нөөц бодис багатай үрээс туяхан цухуйц гарах улмаар ган халуун болон тааламжгүй нөхцөлд амархан нэрвэгдэж, ургац буурах үндэс болж байна. Ургамал газар тариалангийн хүрээлэнгийн үр тарианы селекцийн секторын туршлагын талбайд зусах буудайн эрт болцтой Дархан-131, Дархан-160 дунд болцтой Дархан-34, Дархан-193, дунд оройн болцтой Дархан-144, Дархан-181 сортуудын үрийг EML200 фракцлагч машинаар <2.0 мм, 2.2 мм, 2.5 мм, 2.8 мм, 3.0 мм< диаметрээр 5 фракцад ангилан шигшиж, 1 м2 дэвсэгт 3 давталтаар 3.5 сая ширхэг нормоор 6 см гүнд гараар тариалж хээрийн цухуйц, ургац ургацын бүтцийн үзүүлэлтийг улсын сорт сорилтын арга зүйгээр тодорхойлов. Хээрийн цухуйц ба ургацад үрийн фракц /F=(2.374, P≤0.00), сортын онцлог /F=(34.432, P≤0.00), сорт х фракцын харилцан үйлчлэл /F=(20.774 P≤0.00) бодитой нөлөө үзүүлж байлаа. Судалгааны дүнгээр хээрийн цухуйц 2.2 мм-ээс дээш фракцын үрээр тариалсан хувилбар 7.3-15.0%-иар нэмэгдэж харин 2.2 мм-ээс бага фракцаар тариалсан хувилбарт 14.4-27.3%-аар буурч байна. Үрийн фракцыг 2.0 мм-ээс 2.8 мм болж томроход ургац 4.9 ц/га нэмэгдэж байна. Регрессийн шинжилгээгээр үрийн фракцыг 0.1 мм-ээр нэмэгдүүлэхэд ургац дунджаар 2.12%-аар нэмэгддэг байна. Сортуудын хувьд үрийн хэмжээ томроход хээрийн цухуйц ба ургац нэмэгдэх бөгөөд ялангуяа дунд болон дунд орой болцтой сортуудад илүү нэмэгдэж байна. Буудайн эрт болцтой сортыг 2.2 мм, дунд болон дунд орой болцтой сортыг 2.5 мм-ээс дээш үрээр тариалах нь тохиромжтой байна. Түлхүүр үг: зусах буудай, сорт, үрийн фракц, хээрийн цухуйц, ургац